Translation Solutions for Sustainable Collocations of the English Political Mass Media Discourse - E. V. Terekhova; A. V. Zban (Научный диалог)
The article discusses the issues of syntactic-semantic solutions of fixed collocations translation. A review of collocation samples under study has been performed; and their definition has been given. The authors undertake a comparative analysis of the collocations in the process of their translation from English into Russian. The results of the functioning of the phrases studied in the English-language political mass media texts have been presented. Particular attention is paid to such word combinations that make up the periphery of phraseology. This approach is the authors development of the topic of the collocations. It is shown that the latter have not yet fully adopted their final form of use. The authors also assume that the collocations under analysis have not yet been recorded in the dictionaries. This is the core point of the authors’ development. The novelty of the study is seen in the fact that for the first time the presence of the related meaning of one of the components of such collocations is formulated. It is concluded that its direct and figurative meanings cannot but affect the translation solutions. The authors argue that the probability of borrowings and metaphorization among such word combinations is very high. The classification of models of formation of these constructions has been proposed. The relevance of the study can be explained by the difficulties of their rendering. The authors of the article offer their innovative approaches of translation solutions of mass media collocations under study.